Study of Adoption of Open-Source Solutions in India - Khare, Vivek (Digital Repository of Theses, 2024)
This study attempts to investigate the impact and general application of open-source technologies in Indian IT enterprises. The adoption, cost-effectiveness, customization, security, collaboration, and policy framework concerns associated with open-source technology are the primary research difficulties in this specific context. Through addressing these issues and providing important viewpoints for strategic decision-making and enhanced adoption of open-source technology in Indian IT companies, the study aims to close the gaps in the existing literature. To enable a thorough understanding of the adoption and use of open-source technology, the study framework uses a mixed-methods approach that combines quantitative and qualitative approaches. We gathered the quantitative data through random sampling and the qualitative data through purposive sampling. To uncover underlying factors and patterns, the data underwent statistical analysis, such as factor analysis. The researcher verified the variable's collinearity using the KMO and Bartlett tests. The researcher used subsequent exploratory factor analysis (EFA) to identify unidentified variables influencing the acceptance and effects of open-source technologies. In order to augment the results of the study and guarantee a large enough sample size, the researcher contacted experts in the field. To learn the particular underlying causes of the phenomena, the researcher also carried out in-depth interviews. The results of the study revealed that adopting and using open source presents many difficulties for IT workers. The findings also revealed the comments of respondents regarding risk management and security issues when using open-source technologies. The study's highlights, conclusions, and discussion facilitate stakeholders', legislators', and industry practitioners' better knowledge of how to effectively prepare and maximise open-source technology adoption plans. The ultimate objective of the study is to facilitate the successful use of open-source technologies by Indian IT enterprises, thereby promoting innovation, collaboration, and strategic alignment with global market trends.